Risk Assessment of Heavy Metal Contamination in Fresh Vegetables from Markets in Luoyang City, China - Yuan Wang, Fa; Shui Zhang, Chang; Feng Xu, Xiao (Asian Journal of Chemistry, 2011)
Consumption of vegetables contaminated with heavy metals has been identified a major food chain route for human exposure. Heavy metal concentrations in 15 species of fresh vegetables from markets in Luoyang City were investigated. The results showed that mean concentrations of Pb in wax gourd, pumpkin, potato, carrot and lettuce and mean Cd concentrations in pumpkin, marrow, tomato, green pepper, potato, carrot and lettuce exceeded the permissible limits in China. The maximum concentrations of Pb and Cd were both found in potato, exceeding the permissible limits in China by 17.0 times and 2.9 times, respectively. Generally, Cd and Pb were the commonest metal pollutants, particularly in root-stem vegetables. Cu, Zn, Ni and Cr concentrations were all below the permissible limits. The results of health risk assessment showed that Cd and Pb had potential health risk for both adult and children consumers, while Cu, Zn, Ni and Cr were generally safe.